A argumentação em textos dissertativo-argumentativos no 9º ano do ensino fundamental com o uso da plataforma web Rapi10 - Teixeira, Clair da Silva (2019)
The work of research, entitled The argumentation in dissertative-argumentative texts in the 9th grade of elementary school using the Rapi10 web platform, was developed in the city of Canindé/CE. The problematic that gave rise to the research was the concern as a teacher of Portuguese Language regarding the gap presented by students of Basic Education regarding aspects related to argumentation. The lack of argumentation becomes quite evident due to the accomplishment of an essay of the dissertative-argumentative genre during the Enem process, at the end of Basic Education. This exam has 5 competences. We are interested in competencies II - which deals with understanding the proposal and the structure of the wording, III - which deals with the way we select, relate, organize, and interpret information and facts in defense of a point of view, and IV - which deals with of the use of linguistic mechanisms to construct the argument. For our research, we used as main theoretical references Perelman and Tyteca (2005), who deal with the New Rhetoric, based on Aristotle's rhetoric; Adam (2011, 2019), who deals with the concepts of textual sequences, and Koch and Elias (2004, 2015a, 2015b, 2015c, 2015d, 2016, 2017a, 2017b and 2017c), who give a didactic treatment to questions that permeate the textual linguistics. In the metodology of the study, action research was used as an instrument to perform the work, as we understand it to be the most suitable method to improve teaching. Given the relevance of the use of technologies for education, during the application of the activities, we use a web tool Rapi10, idealized by the researcher, with a 9th grade class consisting of 18 students. In addition to intensifying the productions from a higher productivity due to agility in correction and feedback to students, it works as a pedagogical support for the teaching of the dissertative-argumentative genre. In addition, it serves as a pedagogical accompaniment through graphs and PDF reports generated by the system itself. The result of the work was very significant, since, in the first production, the average grade was 444.39 points and, after the work developed, increased to 708.61 points, evidencing the improvement of the argumentative strategies in the competences II, III and IV, such as the presence of a thesis and arguments aimed at its defense, a better selection, organization and hierarchy of these and a variety regarding the use of diverse linguistic mechanisms.